Honour, Masculinity and Corporality in the Officer Corps of Early Eighteenth-Century Sweden - Ville Sarkamo (Sjuttonhundratal, 2010)
Military honour and physical commitment to serve king and fatherland played a central role in the ideals of the army of Charles XII of Sweden. These ideals were formed within a culture in which the role of the warrior, dictated by a code of honour, was constantly challenged. My main empirical primary sources consist of the archivale records of the Swedish Diet, which included Placement Committee records from the Diet of 1723. An honourable man had the right to a livelihood and a respectable position in society. My aim is to show that, in order to obtain such a position, a military man had to present himself as someone who had offered his body in the service of his king and country. An appeal to one’s merits in battle was the best way of defending a claim to a post, because bravery in combat was the most respected virtue in military life. Those officers who had clear proof of their bravery, especially in the form of combat wounds, were in the best position. In this sense, honour and the body were closely linked.